ANALISIS KEWENANGAN KSOP KELAS IV MUARA ANGKE DALAM KESELEMATAN PELAYARAN PELABUHAN MUARA ANGKE - Aszahra, Kuni Nela Rizki; Rahardiansah, Trubus; Notoprayitno, Maya Indrasti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The Class IV Port Authority and Harbor Office (KSOP) of Muara Angke plays a crucial role in overseeing maritime safety at Muara Angke Port, North Jakarta. With the increasing maritime activities, the challenges faced in enforcing safety regulations have become more complex. This study aims to analyze the obstacles encountered by KSOP in ensuring navigation safety and to recommend strategic measures to enhance oversight effectiveness. The findings of this research indicate that challenges include limited human resources, weak law enforcement, and a lack of public awareness regarding the importance of maritime safety. Strengthening regulations, promoting safety awareness, utilizing modern technology, and collaborating with related agencies are necessary steps to create a safer maritime environment and prevent maritime disasters. Through these measures, it is expected that KSOP Class IV Muara Angke can enhance its authority and foster a better safety culture among maritime stakeholders.Keywords : Maritime Safety, KSOP Class IV Muara Angke, Port Supervision.